Electrochemotherapy and Simultaneous Photodynamic Bone Stabilization of Upper Limbs in Metastatic Renal Cancer Disease: Case Report and Literature Review - Ugo Albertini; Andrea Conti; Nicola Ratto; Pietro Pellegrino; Michele Boffano; Raimondo Piana (Case Reports in Medicine)
Introduction. Metastatic bone disease represents a systemic pathology that heavily affects the quality of life of oncologic patients causing pain and functional disability. Methodology. We present the case of a patient with a history of renal cell cancer presenting pathologic fractures of both humeri and proximal right radius. Results. After a careful multidisciplinary approach, an adjuvant anticancer therapy and a photodynamic bone stabilization procedure were performed with a minimally invasive technique aiming to minimize pain and local disease progression, while restoring functional autonomy and improving the patient’s quality of life. Electrochemotherapy was delivered on the lytic bone lesions with extraskeletal involvement of the proximal left humerus and the proximal right radius, and then polymeric bone stabilization was performed on both humeri. At two months of follow-up, the patient presented satisfactory functional scores (MSTS score: 12/30 bilaterally; DASH scores: 46.7/100 for the right side and 48.3/100 for the left one), and pain was well controlled with opioid analgesics. Radiographs showed good results in terms of ossification of lytic bone lesions and durability of polymeric stabilization. At four months of follow-up, the patient reported a stable clinical scenario. Six months after surgery, due to extremely poor prognosis after the progression of primary disease, the patient was referred to palliative care and died shortly thereafter. Conclusion. Over the last decade, the management of metastatic bone disease has changed. Low-toxicity and minimally invasive procedures such as electrochemotherapy and polymeric bone stabilization might be performed concomitantly in selected patients, as an alternative to radiation therapy and to more demanding surgical procedures such as plating and adjuvant cementing.